Sediment characteristics of some Nova Scotian beaches - Bryant, Edward (Atlantic Geology)

(untitled) (Maritime Sediments Editorial Board, 1983)
A general model exists relating morphology, hydrodynamics and sediment transport behaviour of beach foreshores. This model states that on a reflective foreshore, where wave energy is reflected from the beach face, sediment size grades steeply in value (0.2 mm/km) along the beach face, downdrift and towards highest energy. This grading is temporally stable. On a dissipative foreshore, where wave energy is dissipated across a surf zone, size gradings are weakly developed (0.1 mm/km) and have a high degree of temporal variability. The model applies to high energy, swell-dominated, compartmentalized beaches with stable sea level and no sediment input. Most of the beaches studied in Nova Scotia, where sea level is rising, fit within this model; however the effects of source dominance, low wave energy levels and edge wave triggering processes must be considered.